“No Hijab in Workplace”: Discrimination against Muslim Women Employees in Indonesian Property Companies - Siti Nur Fitasari; Fuad Mas’ud (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The challenges of injustice faced by Muslim Women Employees who wear the hijab in the workplace still occur and have an impact on undeveloped career paths and low-paying job positions. Certain job positions do not require Muslim Women to wear the hijab, and some companies ask Muslim women who wear the hijab to take off their hijab. This research aimed to explore the challenges experienced by Muslim Women Employees who wear the hijab in their career paths and job positions at three property sector companies in Tangerang, Bekasi, and Semarang. The research was conducted using a qualitative phenomenological study method, and there were four informants from property companies in the Bekasi area, three people from property companies in the Tangerang area, and three from property companies in the Semarang area. The results of this study show that the forms of challenges experienced by the informants impacted their performance. Thus, the informants chose to resign from their jobs, and only one informant changed divisions. The study results also show that Muslim Women Employees who wear the hijab experience career stagnation due to non-objective assessments by superiors who do not like the way their hijab.